Neurobehavioral disorders in a patient diagnosed with posttraumatic stress disorder and undifferentiated schizophrenia. Clinical case of low prevalence and incidence in Colombia (2018)
Introduction: Post Traumatic Stress Disorder (PTSD) is a neuropsychiatric disorder that is characterized by being exposed to traumatic events such as forced displacement, armed conflict and clinical manifestations of low self-related emotional disorders such as anxiety, depression and apathy, which affect the deterioration of the quality of life, neurocognitive functioning and self-perception of their physical and mental health. Objective: to identify the neuroconductual alterations that presents a subject diagnosed with PTSD and undifferentiated schizophrenia. Clinical case that tends to present low prevalence at clinical level, especially in the Colombian Suroccidente. Method and materials: Participant: male patient 35 y old, single, right-handed, low schooling. Retired military man diagnosed with PTSD for having been exposed to war. With a clinical picture of undifferentiated paranoid type schizophrenia, accompanied by visual, auditory hallucinations and disinhibitory behavior. Magnetic resonance imaging showed presence of focal lesions in the frontal lobe (executive functions) temporal lobe (memory) and hypodensity in the somatosensory cortex. It was applied an assessment protocol for clinical neuropsychology comprised of the following tests Mini-Mental State Examination-MMSE, severity scale symptoms of post-traumatic stress disorder, digit span scale Wechsler, geriatric depression scale of Yesavage. Anxiety inventory beck, trail making test (Form A/B), history of Babcock, test clock, frontal assessment battery, verbal fluency, general health questionnaire, Barthel index and scale Lawton and Brody for instrumental activities of daily life. Results: The patient has a mixed clinical picture of depression and anxiety, clinically correlated with the deterioration posing in neurocognitive functioning, especially in executive functioning tasks (tasks inhibition) and the deterioration in their quality of life. Discussion: The data obtained show that the subject needs intervention plans functional neurorehabilitation immediately. This clinical case shows the consequences that the war usually generates in people. It is necessary that the national, local and regional government establish true mental health policies, those of now only reflect the inefficiency and incompetence of the government on duty. © 2018, Scientific Publishers of India. All rights reserved.